Categorizing open answers in the DRM module of SOEP-IS - Tobias Wolf (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
This paper documents the categorization of open answers in the diaries of the Day Reconstruction Method (DRM) module of the SOEP Innovation Sample (SOEP-IS) for employed and unemployed workers. Respondents of the module reported either 1 out of 23/25 listed activities or a self-selected description of an activity during the previous day. By assigning the open answers either to the initially listed categories and by defining new categories for a subset of open answers enriches SOEP-IS DRM by more than 1,700 additional categorized episodes for quantitative analysis.
Keywords: 330; Day Reconstruction Method; DRM; open answers; SOEP-IS